Carry-over and consequences of social connections amongst wild birds - Firth, J (2016)
Ecological factors are known to influence the spatial distribution of individuals, which in turn governs social structure. However, social interactions can have important individual- and population-level consequences and may shape various ecological processes (Chapter 1). In this thesis, I examine the factors shaping social networks amongst wild birds (Paridae). I demonstrate that these social connections are biologically important, and influence numerous processes, including spatial structure itself. First, I demonstrate that both the spatial occurrence and dynamic social decisions of individuals underpin the non-random composition of foraging flocks (Chapter 2). Reciprocally, I show that the spatial arrangement of individuals’ breeding locations is predicted by the previous winter's social network, as birds breed nearer to, and share territory boundaries with, those they held the strongest connections to (Chapter 3). I then use experiments to directly assess the consequences of social structure. I show that birds exhibit compensatory shifts in their social network position upon removal of their flock mates (Chapter 4). Following this, I introduce a novel experimental system that automatically controls which individuals could feed together. These externally-imposed foraging constraints cause social segregation at non-experimental food patches (Chapter 5), which also carries over into breeding site prospecting (Chapter 5). I show that social information transmission, regarding the location of novel food patches, also changes to correspond to the experimentally imposed social network structure (Chapter 6). Furthermore, social foraging associations are found to influence social learning, as birds appear to prioritise learning from those who provide relevant information on a regular basis. Finally, I demonstrate that birds choose to forgo maximising their own food intake to sustain their relationships (Chapter 7). Through prioritising their pair-bond over their own preferences, this also changes the social composition of foraging flocks, indicating how a single relationship can govern wider social network position. Additionally, I show how social relationships can influence individual behavioural plasticity and the learning of foraging strategies. This thesis thus contributes to elucidating the relationship between spatial structure and social networks within wild populations. It also demonstrates how social systems respond to external changes, and the direct causal implications of this for shaping spatial structure, information flow and individuals' social and foraging strategies. Together, these findings form a foundation for expanding our understanding of the ecological and evolutionary implications of social networks and the mechanisms underpinning this (Chapter 8).